Título Padrão - Nomura, Hitoshi; da Costa, Raimundo Saraiva (Arquivos de Ciências do Mar, 2018)
King mackerel, Scomberomorus cavalla (Cuvier), and Spanish mackerel, Scomberomorus maculatus (Mitchill) , are two commerciallyimportant species of fishes from NortheasternBrazil. In a previous paper (Nomura & Costa,1966) , the authors presented the length-weight relationship of the two above mentionedspecies, but in 1965 the fishermen didnot allow dissections o f fishes, and so the da ta made no reference to sex. In 1966 (Nomura,1967 ; Nomura & Rodrigues, 1967) , due tolack of a balance, the weights were not recorded.